Bio-augmentation of heterotrophic bacteria in biofloc system improves growth, survival, and immunity of Indian white shrimp Penaeus indicus. Issue 98 (March 2020) - Panigrahi, A.; Das, R.R.; Sivakumar, M.R.; Saravanan, A.; Saranya, C.; Sudheer, N.S.; Kumaraguru Vasagam, K.P.; Mahalakshmi, P.; Kannappan, S.; Gopikrishna, G.
Abstract: Effect of bio-augmentation of Bacillus spp in biofloc on growth, survival and immunity in Indian white shrimp Penaeus indicus was evaluated. Nine Bacillus strains were isolated and screened individually as well as in the form of a consortia. To maintain a C:N ratio of 12:1 a blend of carbohydrate sources was used. Bio-augmentation with bacterial consortium and Virgibacillus sp. produced improved growth and immunity. Shrimp survival ranged from 80 to 95% among treatments. Production was higher (35%) in the biofloc tanks with an average body weight (ABW) of 10.89 ± 1.2 g. On evaluating the immune responses, it was found that trypsin significantly (P < 0.05) enhanced Prophenoloxidase (PO) activity in Lysinibacillus, Bacillus cereus, Bacillus licheniformis and Bacillus subtilis bio-augmented groups. Laminarin induced PO activity was observed in groups supplemented with Oceanobacillus sp., Bacillus sp. and Bacillus megaterium . The lysozyme (LZ) activity was significantly (P < 0.05) higher in B. cereus and Microbial Consortia (MC), while other treatments were less effective. Total hemocyte count (THC) significantly (P < 0.05) increased in all treatment groups compared to the control. Hyaline hemocyte (HH) count was significantly (P < 0.05) higher in the control group (14.43%). Semi granular hemocytes (SGH) was higher in groups treated with Lysinibacillus, Bacillus sp., B. licheniformis and B. subtilis. The granular hemocyte (GH) count was significantly (P < 0.05) higher in Virgibacillus sp., B. cereus, B.megaterium and Oceanobacillus sp. The biofloc alone (BF), treated and augmented with B. megaterium significantly (P < 0.05) increased phagocytic activity. Highly significant phagocytic index (PI) was observed in bio-augmented groups, BF and MC. The relative expression levels of immune genes were found to be significantly up-regulated in shrimps grown in bio-augmented groups. Enhanced immunological parameters implies that bio-augmentation of biofloc with Bacillus spp. improved immunity in shrimps. Hence, bio-augmentation of probiotics in biofloc may be useful in improving culture conditions to produce P. indicus. Highlights: Bio-augmentation effect of Bacillus spp. in biofloc on growth, survival and immunity in Penaeus indicus evaluated. Nine Bacillus strains were isolated and screened individually as well as in the form of a consortia. Enhanced immunity and growth suggested that bio-augmentation improves P. indicus production.